The mechanisms involved in formation of deletions and duplications of 15q11-q13. Issue 2 (February 1998) - Robinson, W P; Dutly, F; Nicholls, R D; Bernasconi, F; Peñaherrera, M; Michaelis, R C; Abeliovich, D; Schinzel, A A
Abstract : Haplotype analysis was undertaken in 20 cases of 15q11-q13 deletion associated with Prader-Willi syndrome (PWS) or Angelman syndrome (AS) to determine if these deletions arose through unequal meiotic crossing over between homologous chromosomes. Of these, six cases of PWS and three of AS were informative for markers on both sides of the deletion. For four of six cases of paternal 15q11-q13 deletion (PWS), markers on both sides of the deletion breakpoints were inferred to be of the same grandparental origin, implying an intrachromosomal origin of the deletion. Although the remaining two PWS cases showed evidence of crossing over between markers flanking the deletion, this was not more frequent than expected by chance given the genetic distance between proximal and distal markers. It is therefore possible that all PWS deletions were intrachromosomal in origin with the deletion event occurring after normal meiosis I recombination. Alternatively, both sister chromatid and homologous chromosome unequal exchange during meiosis may contribute to these deletions. In contrast, all three cases of maternal 15q11-q13 deletion (AS) were associated with crossing over between flanking markers, which suggests significantly more recombination than expected by chance (p = 0.002). Therefore, there appears to be more than one mechanism which may lead to PWS/AS deletions or the resolution of recombination intermediates may differ depending on the parental origin of the deletion. Furthermore, 13 of 15 cases of 15q11-q13 duplication, triplication, or inversion duplication had a distal duplication breakpoint which differed from the common distal deletion breakpoint. The presence of at least four distal breakpoint sites in duplications indicates that the mechanisms of rearrangement may be complex and multiple repeat sequences may be involved.